Pengaruh Konsumsi Jus Tomat terhadap Kenaikan Kadar Hemoglobin pada Ibu Hamil Trimester III dengan Anemia di RSUD Ciawi Tahun 2022 - Suci Dwijayanti Lestari; Yenny Aulya; Retno Widowati (Universitas Baiturrahim, 2022)
Anemia in pregnancy has a bad impact and can lead to death for both mother and baby. From the maternal side, a pregnant woman who suffers from anemia during pregnancy or antepartum is susceptible to abortion, premature delivery, antepartum bleeding and is also susceptible to infection. Regular consumption of tomatoes is said to help prevent anemia. The content of vitamin C in tomatoes is needed by the body to maximize the absorption of iron from other foods. This study aims to determine the effect of tomato juice consumption on the increase in hemoglobin levels in third trimester pregnant women with anemia in Ciawi Hospital. The design in this study was a quasi-experimental (quasi-experimental) using a two-group pre-test and post-test design. The population in this study were 45 pregnant women in the third trimester with anemia who performed ANC at Ciawi Hospital in 2022, taken by purposive sampling technique based on inclusion and exclusion criteria. The number of samples used is 30 respondents. The control group consisted of 15 respondents and the intervention group consisted of 15 respondents. Data analysis used paired sample T-Test. From the results of the study, it is known that the average initial hemoglobin level in the experimental group is 9.833 g/dl which is classified as mild anemia, while the final average hemoglobin in the experimental group is 12,913 g/dl which is classified as not anemic. The p-value of 0.000 < (0.05) means that Ho is rejected and Ha is accepted, namely the effect of consumption of tomato juice on the increase in hemoglobin levels of pregnant women. There is a significant effect of consumption of tomato juice on the increase in hemoglobin levels in third trimester pregnant women with anemia. It is hoped that this can be used as a lesson in preventing anemia using tomato juice as an alternative, especially for pregnant women